Early Failure Secondary to Noncoronary Leaflet Prolapse in a Stentless Aortic Bioprosthesis - Cherian, Sanjay (Texas Heart Institute, 2012)
Structural degeneration is an important long-term disadvantage of biologic prostheses. However, early failure of these prostheses is uncommon and is usually caused by rapid calcification. We report the successful management of a rare case of early failure of a stentless aortic bioprosthesis (within 4 months of implantation). The patient presented with severe noncalcific aortic regurgitation secondary to prolapse of the noncoronary leaflet. In consideration of the acute nature of failure in this new-generation bioprosthesis and its unclear cause, we believe that this report, albeit of a single case, warrants some attention.